The Effect of TikTokshop Liveselling on Consumer Buying Interest - Nabila Nur Fitriani (International Journal Administration, Business & Organization, 2022)
The development of digital technology caused developments in the marketing of the industrial world to accelerate, and many companies have started liveselling for their marketing. The purpose of this study was to determine the effect of live selling on buying interest in Bandung State Polytechnic students. The sample used in this study was 100 respondents who are users of the TikTok application and have watched live selling on the TikTok application. This research uses descriptive analysis method, validity test, reliability test, correlation analysis, and simple regression analysis. Data collection used a questionnaire which was distributed via social media to students who use the TikTok application and have watched live selling on it. In this study, the results obtained were 31.1% of the influence of live selling on buying interest. Meanwhile, 68.9% is influenced by other variables not discussed in this study. The results of this study indicate that live selling on TikTok Shop has an influence on consumer buying interest.